Contagion between liquid and illiquid assets during the financial crisis: Evidence from the US credit derivative market - Jungmu Kim; Yuen Jung Park (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2020)
This study aims to investigate the existence of contagion between liquid and illiquid assets in the credit default swap (CDS) market around the recent financial crisis. The authors perform analyses based on vector autoregression model and the dynamic conditional correlation model. The estimation of vector autoregression models reveals that changes in liquid CDS (LCDS) spreads lead to changes in illiquid CDS spreads at least one week ahead during the financial crisis period, whereas the leading direction is reversed during the post-crisis period. Moreover, the results are robust after controlling for structural variables which are proven as determinants of CDS spreads and are empirically supported. This study interprets that information was incorporated first into the LCDSs because of the flight-to-liquidity during the recent crisis period but there is a default contagion effect by reflecting illiquidity-induced credit risk after the crisis. Finally, the dynamic conditional correlation analysis also confirms the main results.
Keywords: G12; G14; 330; Credit default swap; Contagion; Dynamic conditional correlation; Flight-to-liquidity; Granger causality; Granger causality